Baltimore : A Political History - Crenson, Matthew A., 1943- (Book collections on Project MUSE., 2017)
"People from Baltimore glory in its quirky charm, small-town character, and history of North-cum-South culture. Not every native, however, realizes that for much of the nineteenth century, as "mobtown," the city often made its case for being one of the most violent places in the country. Since the death of Freddie Gray in police custody last year, Baltimoreans and the entire nation again focus on the rich and tangled narrative of black-white relations in the city, which once offered an example of slavery existing side by side with the largest community of free blacks in the United States. A distinguished political scientist who spent much of his youth and the large part of his professional career in Baltimore here examines the politics, structure of governance, and role of racial difference in the history of Baltimore, from its founding in the mid-eighteenth century to the recent past. How do we explain its distinctive character? Matt Crenson argues that the city's longtime dependency on the general assembly for a wide variety of urban necessities--the by-charter weakness of its municipal authority--forced residents to adopt the private and extra-governmental institutions that shaped early Baltimore--leading to curious political quarrels over loose pigs, for example, but also to Baltimore's comparative radicalism during the Revolution. Meantime, whites competed with blacks, slave and free, for menial and low-skill work, and an urban elite found a way to thrive by avoiding, wherever possible, questions of slavery vs. freedom, just as, long after Civil War and emancipation, it preferred to sidestep racial controversy. Crenson thus holds up a mirror to Baltimore, asking whites in particular to re-examine the past and accept due responsibility for future racial progress."--Provided by publisher